Environmental economics – a modern science with traditions - Korporowicz, Violetta (Studia Ecologiae et Bioethicae, 2020)
The fact that problems of environmental degradation and its protection are gaining importance is caused, among others, by limitations in management efficiency. It forces us to look at economic processes with consideration of output of such disciplines that indicate how one should manage in a situation of reduced availability of natural resources. Such discipline, without any doubts, is environmental protection. This science indicates methods and economic instruments that can be applied in economic practice necessary for environmental protection. It deals also with problems related to economic studies of implications of environmental policies. At the same environmental economics that results from neoclassical trend of economics looking at the market as unfailing mechanism of economic regulation proves that invisible hand of market fails in case of environmental protection. That is why we should apply different types of instruments especially these related to indirect regulation (including such economic instruments as taxes) that support actions related to limitation of environmental degradation. It is worth also to add that recognition of methodological premises of this science supports not only development of this discipline but first of all it shows that it is applicable. The principles developed by environmental economics should be applied in practice by all participants of economic life from consumers and to producers and governments in order to keep not only current natural resources but most importantly ensure the development opportunities for next generations.